Mobilogue: Creating and Conducting Mobile Learning Scenarios in Informal Settings (International Conference on Computers in Education, 2013)
Mobilogue is a tool to support educators and students in authoring and deploying learning support with location awareness and guidance to mobile devices. The application area of the framework covers informal learning settings like field trips, museum visits as well as formal classroom settings. The focus of the framework is on the simplicity and flexibility of the domain independent content authoring and content deployment. We present an authoring tool that uses a workflow-related, graph-based paradigm to model and author a path across different locations. Locations relate to physical places or artifacts through QR codes and provide supportive information. The guidance takes place by identifying the user’s location by scanning the QR codes and visualizing the appropriate information on the smartphone. Finally we describe possible scenarios for such informal learning settings and report on an evaluation of one scenario authored by students for a museum.